First of a line or last of a dynasty? Parabos tigneresi and the evolution of eurasian bovinae in the early pliocene - Leonardo Sorbelli; Faysal Bibi; Joan Madurell-Malapeira; Federica Grandi; Elena Moreno-Ribas; Oriol Oms; Gerard Campeny; Bruno Gómez de Soler (PLoS ONE, 2026)
The Early Pliocene maar deposits of Camp dels Ninots (Catalonia, NE Iberia) have produced an exceptionally well-preserved fossil assemblage. Among the large mammals, a large bovid stands out, represented by 14 individuals, including 8 nearly complete and partially articulated skeletons. Here we provide a comprehensive description and systematic evaluation of this material, previously referred to Alephis tigneresi , including an in-depth comparison with specimens assigned to Parabos , Alephis , and other large Late Miocene and Early Pliocene Eurasian and African bovids. We revise the genera Alephis and Parabos , recognizing five valid species across both groups, and refer the Camp dels Ninots bovid to Parabos tigneresi . We further explore the possible relationships of Parabos and Alephis within Bovinae, finding that they could either be the earliest European representatives of stem Bovini or among the last surviving members of the Miocene Tragoportacini radiation. Additionally, the exceptionally preserved skeletons of P. tigneresi provide paleoecological evidence of adaptation to humid, vegetated environments, confirming reconstruction of the paleoenvironment of the Camp dels Ninots maar lake, while also showing traits associated with mixed to open habitats, suggesting potentially broad habitat preferences for P. tigneresi .